The Effect of Locally Administered Pamidronate on Autogenous Bone Graft in Maxillofacial Reconstruction: A Randomized Clinical Trial - Bayat, M. (Int J Organ Transplant Med, 2017)
BACKGROUND: Although bone grafts are commonly used in reconstructive surgeries, they are sensitive to local perfusion and are thus prone to severe resorption. Biphosphonates can inactivate osteoclasts and can be used to control the undesirable bone resorption. OBJECTIVE: To assess the effect of administration of biphosphonates on bone resorption. METHODS: 20 patients with bony defects who were candidates for free autogenous grafts were randomized into “pamidronate” and “control” groups. Bone segments were soaked in either pamidronate solution or normal saline and were inserted into the area of the surgery. Bone densities were measured post-surgery and in 6-month follow-up. Data were obtained via Digora software and analyzed. RESULTS: The mean±SD bone density in pamidronate group changed from 93.4±14.6 to 93.6±17.5 (p<0.05); in the control group the density decreased from 89.7±13.2 to 78.9±11.4 (p<0.05). The mean difference of bone density in anterior areas of the jaws showed higher DXA in comparison to posterior regions (p=0.002). CONCLUSION: Locally administered pamidronate affects reduction in bone resorption.